Den nøgne skrift: Myter om at skrive - Christophe, Nirav; Branth, Janicke (Peripeti, 2021)
In this article Nirav Christophe presents a critical reflection on the many myths of playwriting, leading the reader from systematic reflections on playwriting to concrete examples.